Systematic Literature Review of Switching Behavior in Service Industry - Stella Olivia Rawis; Reza Ashari Nasution; Laksmi Saraswati Hadiansyah; Widyoretno Adiani; Atik Aprianingsih (Binus Business Review, 2022)
Although many studies have focused on consumer behavior, a summary of constructs specialized in switching behavior is unexplored. The research aimed to enlarge an extensive and updated overview of customer switching behavior in the service industry. The Systematic Literature Review (SLR) technique evaluated 35 scientific papers released from 2011 to 2021 to analyze drivers, mediating factors, moderating factors, and outcomes related to customer switching behavior. The results improve the understanding and outcome of the drivers to retain consumers. First, the drivers (independent variables) consist of social factors, firm factors, customer behavior, and cost. Second, mediating factors include switching cost, experiential psychological states, inertia, emotion, and consumer perception. Third, moderating constructs have mooring factors, satisfaction, and inertia. Surprisingly, inertia appears in both mediating and moderating variables. The difference depends on service context. Last, outcomes consist of customers’ responses, low satisfaction, and low loyalty. The research contributes to theoretical and managerial implications for sustainable planning by making an overview of several service models. In addition, it includes the drivers of switching behavior in the service industry. Furthermore, the framework offers possibilities and issues for future research and moves the focus from the conventional service domain to social networking that refers to the online platform.